2018
DOI: 10.3390/e20020119
|View full text |Cite
|
Sign up to set email alerts
|

Exergy Analysis of the Musculoskeletal System Efficiency during Aerobic and Anaerobic Activities

Abstract: Abstract:The first and second laws of thermodynamics were applied to the human body in order to evaluate the quality of the energy conversion during muscle activity. Such an implementation represents an important issue in the exergy analysis of the body, because there is a difficulty in the literature in evaluating the performed power in some activities. Hence, to have the performed work as an input in the exergy model, two types of exercises were evaluated: weight lifting and aerobic exercise on a stationary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
(112 reference statements)
1
18
0
1
Order By: Relevance
“…The remaining problem is the gradient of temperature between the core, and the skin which is highly accurate represented by. 15 From these measurements, it is possible to use the stationary bicycle to have the performed work 11,12 and properly evaluate the traditional models of heat and enthalpy transfer to the environment 15 which are highly validated for basal conditions. Eventually, the relations of different researchers of several fields, mechanical engineers (thermodynamic and heat and mass transfer area) and medical doctors (from sports and orthopedic field) have been increasing the relation with two areas with similar objectives, although with a completely different language.…”
Section: Results Of Previous Analyses and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining problem is the gradient of temperature between the core, and the skin which is highly accurate represented by. 15 From these measurements, it is possible to use the stationary bicycle to have the performed work 11,12 and properly evaluate the traditional models of heat and enthalpy transfer to the environment 15 which are highly validated for basal conditions. Eventually, the relations of different researchers of several fields, mechanical engineers (thermodynamic and heat and mass transfer area) and medical doctors (from sports and orthopedic field) have been increasing the relation with two areas with similar objectives, although with a completely different language.…”
Section: Results Of Previous Analyses and Future Workmentioning
confidence: 99%
“…Eventually, it was performed a comparison of two tests in which the power executed by the body is a known variable: bicycle stationary ergometric test and weightlifting 11 . Results indicated that the use of a stationary bicycle is the best option to establish a method to experimentally evaluate the thermal behavior of the human body 11 .…”
Section: Experimental Procedures and Difficultiesmentioning
confidence: 99%
“…In recent years, numerous studies have been published on thermodynamic analysis of processes based on metabolism in the biological systems [7][8][9][10][11][12][13][14][15][16][17][18][19]. However, in the literature, there is a limited number of studies on respiratory thermodynamics [8,10,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several Thermodynamic approaches to biological systems have been performed in the past decades. To cite some, there is the study of a single cancerous cell [ 3 ], protocols in hypothermia techniques [ 4 ], and an analysis of physical activities [ 5 , 6 , 7 ]. There is also a review article gathering these new applications as in Ozilgen [ 8 ].…”
Section: Introductionmentioning
confidence: 99%